2013
DOI: 10.1515/hf-2012-0136
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mobilized copper(II) levels in micronized copper-treated wood by electron paramagnetic resonance (EPR) spectroscopy

Abstract: Sapwood sawdust from southern pine was treated with micronized copper (MC) under various conditions and the mobilized copper(II) (Cu mob ) concentrations were determined in the treated wood by electron paramagnetic resonance (EPR) spectroscopy. The spectral parameters for the copper sulfate (CuSO 4 )-treated sapwood and those of the MC-treated sapwood were very similar. A linear correlation was found between the intensities of copper (Cu) EPR spectra and those of Cu energydispersive X-ray fluorescence spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
3
6
0
Order By: Relevance
“…These data demonstrate an association between the peroxide post-treatment and increased levels of reacted copper. The reacted copper content in the wood treated with micronized copper carbonate is typical of values previously reported [21,25]. The peroxide treatment may generate more reactive sites in the wood, leading to enhanced reaction between the wood and the micronized basic copper carbonate.…”
Section: Copper Characterizationsupporting
confidence: 79%
See 1 more Smart Citation
“…These data demonstrate an association between the peroxide post-treatment and increased levels of reacted copper. The reacted copper content in the wood treated with micronized copper carbonate is typical of values previously reported [21,25]. The peroxide treatment may generate more reactive sites in the wood, leading to enhanced reaction between the wood and the micronized basic copper carbonate.…”
Section: Copper Characterizationsupporting
confidence: 79%
“…The resulting sawdust was analyzed by x-ray fluorescence spectroscopy for total copper. The remaining sawdust from each specimen was analyzed by Electron Paramagnetic Resonance (EPR) spectroscopy at the University of British Columbia (Vancouver, BC, Canada) using the methods developed by Xue et al [21]. A Bruker Elexsis E500 series continuous wave EPR (Bruker BioSpin GmbH, Rheinstetten, Germany) was used for the analysis.…”
Section: Copper Characterizationmentioning
confidence: 99%
“…Detailed methodology was reported by Xue et al (2012Xue et al ( , 2013. A series of sawdust samples treated with CuSO 4 solutions at 16 different concentrations was analyzed by EPR.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies (Xue et al 2010(Xue et al , 2012 confirmed that hydrated Cu species were produced and fixed rapidly with wood upon treatment with an aqueous suspension of BCC. A quantification method based on EPR in combination with X-ray fluorescence (XRF) spectroscopy was developed for determining the reacted Cu concentrations in the treated wood (Xue et al 2013). In the study reported here, this quantification method will also be applied aiming at the investigation of the reacted and total Cu levels in EW and the LW of two Canadian softwoods, which were pressure treated with micronized Cu.…”
Section: Introductionmentioning
confidence: 99%
“…When wood is treated with MC, some Cu reacts with wood and part of it remains in the form of unreacted Cu particles that provide a reservoir effect [ 15 ]. Most of the studies [ 16 ] on Cu bioavailability of micronized Cu have focused on the release of Cu 2+ ions [ 17 – 21 ]. However, the superior efficacy of the treatment [ 22 – 25 ] may be partially due to insolubilized persistent CuCO 3 ·Cu(OH) 2 NPs that diffuse through the fungal cell wall and its membrane and exert their toxic effects, also described as the Trojan horse mechanism [ 26 ].…”
Section: Introductionmentioning
confidence: 99%